The limits of mathematics : a course on information theory and the limits of formal reasoning - Chaitin, Gregory J. ((Springer Series in Discrete Mathematics and Theoretical Computer Science))
Obra sobre los límites de las matemáticas, a través de un curso sobre teoría de la información y los límites del razonamiento formal.